Peran Keuangan Publik dalam Mendukung Pembangunan Berkelanjutan: Tinjauan terhadap Kota Baubau - Sari, Murni; Rahma, Filasti; Fatmala, Wilda; Handayani, Eva (Jurnal Maksipreneur, 2025)
This study aims to analyze the influence of public financial policy, public financial practices, and community participation on sustainable development in Baubau City. This research employs a quantitative design with a survey approach, involving 399 respondents selected using the Slovin formula from a total population of 166,150 individuals. Data were collected through questionnaires using a Likert scale to measure respondents' perceptions of public financial policy, public financial practices, community participation, and sustainable development. Data analysis was conducted using validity and reliability tests, as well as multiple linear regression analysis. The findings show that public financial policies, practices, and community involvement significantly impact sustainable development in Baubau City. These findings underscore the importance of effective, transparent, and participatory financial management in supporting sustainable development. The implications of this study suggest the need for improved implementation of sustainable financial policies and active community participation to achieve more inclusive development goals in Baubau City.